Long-term residual anchorage resistance of gradient anchorages for prestressed CFRP strips. (15th April 2018) - Harmanci, Yunus Emre; Michels, Julien; Czaderski, Christoph; Loser, Roman; Chatzi, Eleni
Abstract: This paper presents findings from a series of experimental investigations on the long-term resistance of the gradient anchorage, a purely epoxy-based non-mechanical anchoring technique for prestressed carbon fiber reinforced polymer (CFRP) strips, after exposure to accelerated ageing conditions. A segment of the complete anchorage solution is simulated by anchoring a prestressed CFRP strip to a concrete block. A custom-designed clamping system on one end allows for maintaining the prestress force constant during exposure to accelerated ageing. Upon such an exposure, the specimens are tested in a conventional lap-shear test setup. Several exposure scenarios and their effect on the residual load carrying capacity are considered, namely the effect of carbonated concrete (CC), freeze-thaw cycles (FTC), as well as their combination. Forces and full-field displacements, the latter by means of a 3D-DIC system, were measured during the prestress-force-release and lap-shear tests. Results indicate a higher anchorage resistance for CC compared to the reference specimens. For both groups a debonding in the concrete substrate was observed. Specimens subjected to FTC exposure suffer from a significant reduction in residual anchorage resistance, as well as a shift in failure mode from a concrete substrate dominated to an epoxy/concrete interface failure. The current knowledge on the residual resistance of gradient anchorage has to be adapted accordingly.